Prevalence of polymorphism (-174 G / C) of IL-6 gene in patients with acute brucellosis and hepatobiliary system damage - Mammad oglu, Elchin Guseynov (Journal of Education, Health and Sport, 2019)
Modern brucellosis is characterized by high variability of clinical symptoms. Its evolution is going in the direction of acute forms increasing, with an early development of focal metastatic and infectious-allergic lesions, which, in their turn, increase the severity of the disease’s course. This testifies to early sensitization development in patients in endemic regions already in the acute phase of brucellosis. The objective: to determine the prevalence of the polymorphism (-174 G / C) of the IL-6 gene in patients with hepatic damages in acute brucellosis in the Republic of Azerbaijan. 178 patients were examined, 120 of them fully met all the criteria for inclusion in the study, so they formed the treatment group. The definition of polymorphism (-174 G / C) of the IL-6 gene was made to all patients. Statistical analysis of the results obtained was performed with "SPSS 20.0" and "STATISTICA 6.0" programs. Among 120 patients with acute brucellosis, the disease of the hepatobiliary system had 43 (35.8%) persons according to the generalization of laboratory and instrumental methods of examination. Genotype C / C IL-6 gene was 4.2 times more frequent in patients with acute brucellosis and liver damage than in hepatic lesions-free persons. It was found that among the carriers of C / C genotype, risk of brucellosis prevalence with hepatic damage is significantly higher (χ2 = 12.26; p = 0.002; OR = 0.97; 95% CI [0.28 - 3.41]), while the carriership of the homozygous genotype G / G, on the contrary, has protective effect on the development of brucellosis (OR = 0.16, 95% CI [0.05 - 0.50]).